2015
DOI: 10.5154/r.rchscfa.2014.08.033
|View full text |Cite
|
Sign up to set email alerts
|

Propagación asexual de Pinus leiophylla Schiede ex Schltdl. et Cham.

Abstract: Postgraduados. Carretera México-Texcoco km 36.5. C. P. 56230. Montecillo, Texcoco, Edo. de México.Correo-e: marcosjc@colpos.mx, Tel.: 595 95 20246 ext. 1454 (*Autor para correspondencia). 4 Universidad Autónoma Chapingo-CRUAN. km 38.5 Carretera México-Texcoco. C. P. 56230. Chapingo, Texcoco, Edo. de México. AbstractT he effect of substrate, type of cutting and indole 3-butyric acid (IBA) concentration on the rooting of Pinus leiophylla cuttings was evaluated with the goal of multiplying progenies of half-si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
11

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 11 publications
0
3
0
11
Order By: Relevance
“…Rosier et al (2005) reported that the Abies fraseri scions from the lower zone of the crown were better for achieving the propagation of this species by rooting stem cuttings. Although grafts and cuttings are different vegetative propagation techniques, there are species like Pinus leiophylla that have been propagated by both methods, and some of the factors that have influenced their success are similar (Cuevas-Cruz, 2014;Cuevas-Cruz et al, 2015). The graft variables of the scions and rootstocks showed no significant effects on the probability of graft death in this study, as the stepwise regression revealed that none of the graft variables significantly affected graft survival (Table 2).…”
Section: Discussionmentioning
confidence: 67%
“…Rosier et al (2005) reported that the Abies fraseri scions from the lower zone of the crown were better for achieving the propagation of this species by rooting stem cuttings. Although grafts and cuttings are different vegetative propagation techniques, there are species like Pinus leiophylla that have been propagated by both methods, and some of the factors that have influenced their success are similar (Cuevas-Cruz, 2014;Cuevas-Cruz et al, 2015). The graft variables of the scions and rootstocks showed no significant effects on the probability of graft death in this study, as the stepwise regression revealed that none of the graft variables significantly affected graft survival (Table 2).…”
Section: Discussionmentioning
confidence: 67%
“…También menciona, que cuando el tejido pierde esta característica de competencia, el flujo polar de auxinas endógenas hacia el sitio de enraizamiento puede ser inhibido y afectar el proceso de inducción de raíces. Por lo que la aplicación de auxinas exógenas es necesaria para mejorar la respuesta al enraizamiento de las estacas de las especies de pino, ya que en ausencia de auxinas exógenas el porcentaje de enraizamiento es bajo (Cuevas-Cruz et al 2015, Rivera et al 2016, Riov et al 2020.…”
Section: Discussionunclassified
“…et Cham. ), pero la concentración óptima de AIB dependió de la especie (Cuevas-Cruz et al 2015;Bautista-Ojeda 2020).…”
Section: Introductionunclassified
“…Rosier et al (2005) reported that the Abies fraseri scions from the lower zone of the crown were better for achieving the propagation of this species by rooting stem cuttings. Although grafts and cuttings are different vegetative propagation techniques, there are species like Pinus leiophylla that have been propagated by both methods, and some of the factors that have influenced their success are similar (Cuevas Cruz, 2014, Cuevas-Cruz et al, 2015.…”
Section: Discussionmentioning
confidence: 99%